Art and Mindfulness Behind Bars. (September 2019) - Rosenbaum, Jill Leslie
Engaging in art and mindfulness activities has been found to have numerous positive effects on individuals regardless of age or setting. In recent years there have been an increased number of these programs finding their way into the correctional system. Research indicates that there are multiple benefits for individuals who are incarcerated that engage in these activities. The purpose of this volume is to highlight some of the successful implementations of art and mindfulness programs within the criminal justice system. The authors included in this issue represent a variety of disciplines from both the social sciences and arts in order to develop multidisciplinary understanding, discussion and potential collaboration.